Tunable and unconventional Fermi arcs of two-dimensional transition-metal dichalcogenide modulated photonic Dirac semimetal - Yang Yang; Qiu Hongye; Bi Ke; Yang Biao (Nanophotonics, 2025)
Fermi arcs are nontrivial surface states that exist in topological semimetals, which exhibit a variety of interesting effects, such as anomalous transport properties and chiral anomaly induced phenomena. Recently, the emerged Two-dimensional transition-metal dichalcogenide (TMDC) shows distinctive optical and electrical properties, makes it a promising platform for efficient modulation of Fermi arcs. By covering TMDC sheets on a photonic Dirac metamaterial (PDS), the quadrupole Dirac point splits into two triple degeneracy points (TDPs), each TDP share one Fermi arc. Through tuning the characteristics of TMDC layers, Fermi arcs and transmissions of PDS can be effectively modulated in multi-degrees of freedom. Unconventionally, we find the Fermi arcs may do not terminate at the degeneracy points but between the two type III TDPs. Fermi arcs with nonlocal effect are also investigated. Furthermore, topological transition from open (hyperbolic-like) to closed (elliptical-like) equi-frequency contours at TDP is also observed. Our findings may provide potential applications in flexible modulation of Fermi arcs with multiple functions.